An aproximation to the Right of Participation in resale works - Rejanovinschi Talledo, Moisés (2017)
This article argues the current challenges of artworks droit de suite, their extension in Peruvian legislation to the manuscripts, and the joint liability of mercantile intermediaries, in order to benefit the authors.